Ecological aspects of American cutaneous leishmaniasis: 6. Man-biting sandfly fauna of a patch of residual forest in the middle and north-eastern region of the São Paulo State, Brazil - Almério de Castro Gomes; José Maria Soares Barata; Eduardo Olavo Rocha e Silva; Eunice Aparecida Bianchi Galati (Revista do Instituto de Medicina Tropical de São Paulo, 1989)
This report shows the phlebotomine vectorial role in the endemic cutaneous leishmaniasis situated in the middle and north-eastern region of the São Paulo, Brazil. Analysis of information encloses a sandfly man-biting fauna of four different patches of residual forest. So, using the human-bait and Shannon trap for a period of one year we have caught 16,869 sandflies. The predominance of Lutzomyia intermedia (85,6%) was clear. Moreover, the low density of Lutzomyia whitmani and Lutzomyia pessoai and their epidemiological implications at present and in the past are discussed. Information about the daily activity of some species is given and we emphasize for the first time, the diurnal activity of Lutzomyia firmatoi in the São Paulo State.